Kayak blade-hull interactions: A body force approach for self-propelled simulations - Banks, J.; Phillips, A. B.; Turnock, S. R.; Hudson, D. A.; Taunton, D. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
A sprint kayak experiences an unsteady flow regime due to the local influence of the paddle. However, kayak designs are usually optimised for steady-state, naked hull resistance. To determine whether unsteady paddle effects need to be included in kayak design, the hydrodynamic interactions between a kayak paddle and a hull are assessed using computational fluid dynamics. A body force model of a drag-based paddle stroke is developed using a blade element approach and validated against experimental data. This allows the paddle-induced local velocities to be simulated without the need to fully resolve the detailed flow around a moving paddle geometry. The increase in computational cost, compared to the naked hull simulation, is 8%. A case study investigating the impact of different paddle techniques on the hydrodynamic forces acting on a self-propelled kayak is conducted. A 0.23% difference in self-propelled resistance was observed, while an estimated 0.5% additional increase can be attributed to paddle-induced draught increases. An estimate of small changes in resistance on race times indicates that reductions of even a fraction of a percent are worth pursuing, indicating that the developed methodology may provide a useful design tool in the future.